2015
DOI: 10.1039/c4ta04667f
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled 3D flower-like perovskite PbTiO3 nanostructures and their application in the catalytic oxidation of CO

Abstract: 3D flower-like PbTiO 3 nanostructures self-assembled with (101) nanosheets have been realized by the hydrothermal treatment of the mixture of the lead and titanium hydroxides under the effect of high KOH concentration. The layered K 2 Ti 6 O 13 formed in situ under the effect of the high KOH concentration plays an important role in the crystallization of the primary PbTiO 3 nanosheets and the further self-assembly of the 3D flower-like perovskite PbTiO 3 nanostructures. The self-assembled 3D flower-like perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The hydrothermal synthesis process of the single-crystalline tetragonal perovskite PbTiO 3 (a) and SEM (b~f) and TEM (g) images for three morphologies of Ti-based perovskite oxide catalysts [78][79][80][81] (color online).…”
Section: 固相研磨法使其在低于600℃的焙烧温度下合成了mentioning
confidence: 99%
“…The hydrothermal synthesis process of the single-crystalline tetragonal perovskite PbTiO 3 (a) and SEM (b~f) and TEM (g) images for three morphologies of Ti-based perovskite oxide catalysts [78][79][80][81] (color online).…”
Section: 固相研磨法使其在低于600℃的焙烧温度下合成了mentioning
confidence: 99%
“…x Fe x O 3-δ nanoparticles perovskites by the flame synthesis, and the results showed that oxygen evolution activity was improved. However, most of the currently reported highefficiency perovskite catalysts for CO oxidation are synthesized in traditional ways, such as coprecipitation [17], hydrothermal [18], and sol-gel synthesis [19]. And the obtained perovskite catalysts need to be calcined at high temperatures, leading to complex operations and low productivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] With one-dimensional (1D) structure-based materials as building units, a variety of self-assembling morphologies such as dandelion-like, 9 ower-like, [10][11][12] urchin-like, 13 peanut-like structures 14 and tube-like structures 15 have been reported. Most of these studies usually rely on spherical superstructures prepared with hydrothermal or solvothermal routes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, due to the controllable size, various types of unique morphology and shape-dependent properties, materials with three-dimensional structures synthesized by large-scale self-assembly of micro-and nanostructured building components have become a hot topic of material preparation. [1][2][3][4][5][6][7][8] With one-dimensional (1D) structure-based materials as building units, a variety of self-assembling morphologies such as dandelion-like, 9 ower-like, [10][11][12] urchin-like, 13 peanut-like structures 14 and tube-like structures 15 have been reported. Most of these studies usually rely on spherical superstructures prepared with hydrothermal or solvothermal routes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation